2019
DOI: 10.1039/c9re00045c
|View full text |Cite
|
Sign up to set email alerts
|

New process for producing butane-2,3-dione by oxidative dehydrogenation of 3-hydroxybutanone

Abstract: Reaction of 3-hydroxybutanone in air has been studied with and without a catalyst under atmospheric pressure and at temperatures between 523 and 673 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Reduction of beef tallow amount decreases the fat aroma intensity which is connected with a presence among others of pyridine 2-pentyl (O'Hare & Grigor, 2005). Also, the volatile compound profiles of grilled samples showed that the addition of βglucan reduces butane-2,3-dione, the diacetyl identified as a buttery flavour (Huchedé et al, 2019).…”
Section: Treatmentsmentioning
confidence: 87%
“…Reduction of beef tallow amount decreases the fat aroma intensity which is connected with a presence among others of pyridine 2-pentyl (O'Hare & Grigor, 2005). Also, the volatile compound profiles of grilled samples showed that the addition of βglucan reduces butane-2,3-dione, the diacetyl identified as a buttery flavour (Huchedé et al, 2019).…”
Section: Treatmentsmentioning
confidence: 87%